Características epidemiológicas de los neonatos con cromosomopatías nacidos en el Hospital Clínico Universidad de Chile. Período 2001-2010 - Pardo V, Rosa; Nazer H., Julio; Ramírez R., Constanza; Faundes G., Víctor; Cifuentes O., Lucía (Revista Hospital Clínico Universidad de Chile, 2013)
Background: Chromosomopathies could be detected in neonatal age. Precous chromosomal aberration diagnosis helps to guide the medical care. Aim: To describe the epidemiological characteristics in newborns with congenital anomalies and chromosomophaties. Patients and methods: All newborns with malformations born, between 1 July 2000 and 31 December 2010, in the Clinic Hospital of the University of Chile are registered, as part of the Collaborative Latin ackground: Chromosomopathies could be detected in neonatal age. Precous chromosomal aberration diagnosis helps to guide the medical care. Aim: To describe the epidemiological characteristics in newborns with congenital anomalies and chromosomophaties. Patients and methods: All newborns with malformations born, between 1 July 2000 and 31 December 2010, in the Clinic Hospital of the University of Chile are registered, as part of the Collaborative Latin American Study of Congenital Malformations (ECLAMC), a case-control study. The diagnosis of chromosomal aberrations was made by cytogenetic studies. Results: In this study period there were 15160 births. 5,5% studied neonates with malformations had chromosomal aberrations (5,5%), Trisomy 21 was the most common anomaly with a rate of 35,6/10,000 births, followed by trisomy 13 with a rate of ,9/10,000 and trisomy 18 with a rate of 4,6/10,000. Conclusions: The most frequent chromosomopathies were the aneuploidies. Among case group there were higher maternal age (P<0,0001), less birth weight (P<0,0015); and more relatives with malformations(P=0,0001).